SKILLED WORKERS SHORTAGES IN THE PRINTING INDUSTRY: PERSPECTIVES FROM INDUSTRY EXPERTS - Norizzati Abd Latif; Noor Azly Mohammed Ali (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The printing industry encounters substantial difficulties stemming from a deficiency of skilled workers, impacting production quality, efficiency, and competitiveness. This article examines the intricate difficulties associated with the skilled workers deficit in the printing sector. It analyze their significant impacts and suggests thorough remedies to tackle the problem. A comprehensive qualitative analysis of interviews with industry stakeholders revealed significant challenges, including employment practices, deficiencies in printing training institutes, and adverse industry perceptions. Challenges related to skilled workers shortages encompass diminished quality, lowered customer satisfaction, and decreased production efficiency. Strategies to mitigate these challenges encompass efficient human resources management, skills enhancement and training programs, technological advancement, and outsourcing. Future challenges, including technological disruption, demographic changes, and sustainability issues, necessitate proactive planning and collaboration to maintain the industry’s viability and competitiveness.